Optical path theory : fundamentals to freeform adaptive optics - González-Acuäna, Rafael G.; Chaparro-Romo, Héctor A. (IOP (Series). Release 22., 2022)
This book is mostly based in an equation that was recently published. The equation is the general formula for adaptive optics mirrors, which was published in January 2021--General mirror formula for adaptive optics, Applied Optics 60(2).